Розробка та дослідження системи автоматичного регулювання температури в холодильнику сусла при виробництві квасу - Селіванов, Тарас Вячеславович; Selivanov, Taras (ЦНТУ, 2025)
Випускну кваліфікаційну роботу присвячено проблемі регулювання температурного режиму в холодильнику сусла при виробництві квасу. В проекті проаналізовано АСУТП виробництва квасу. Виконано розробку структурної схеми системи автоматичного регулювання температурного режиму в холодильнику сусла та обрані її елементи. The final qualification work is devoted to the problem of regulating the temperature regime in the wort refrigerator during the production of kvass. The project analyzed the automated process control system for the production of kvass. The structural diagram of the system for automatic regulation of the temperature regime in the wort refrigerator and its selected elements were developed.
Development and research of a system for automatic temperature control in the wort refrigerator during the production of kvass
Keywords: виробництво квасу; холодильник сусла; система автоматичного регулювання; оптимальний регулятор; production of kvass; wort refrigerator; automatic adjustment system; optimal regulator